Shielding disc backscatter calculations in intraoperative radiotherapy using a Monte Carlo simulation based on the method of energy spectra reconstruction - Adam Ryczkowski; Marta Kruszyna-Mochalska; Bartosz Pawałowski; Grzegorz Bielęda; Agata Jodda; Przemysław Adrich; Tomasz Piotrowski (Scientific Reports)
Abstract The study focuses on validating and applying a Monte Carlo (MC) simulation model to backscatter calculations from the shielding discs used during intraoperative electron radiotherapy (IOERT), particularly in breast cancer treatments. The MC model is developed based on dosimetric data collected under reference conditions and validated by measurements with EBT4 Gafchromic films in a water phantom. The study investigates the dose distributions for 6, 9, and 12 MeV electron beams formed by a mobile AQURE accelerator, comparing scenarios with and without a surgical stainless steel shielding disc. While the shielding disc effectively reduces radiation doses behind it, the backscatter significantly increases doses in tissues immediately in front of the disc. Specifically, the dose at 1 mm in front of the disc increases by 19.8%, 18.4%, and 17.5% were observed for 6, 9, and 12 MeV beams, respectively. The validated MC model provides an accurate tool for predicting dose distributions in complex geometries, enabling improved treatment planning and safety in IOERT applications. The findings underscore the need to consider backscatter effects when shielding discs are used in IOERT. The study suggests further optimization of shielding disc design, potentially incorporating biocompatible, low-Z materials to mitigate backscatter.